Synthesis and characterization of a molecularly imprinted polymer for tetracycline - Bernas, Cynthia V.
The molecularly imprinted polymer (MIP) was prepared by copolymerizing methacrylic acid and ethylene glycol dimethacrylate in the presence of tetracycline as the template. The template was subsequently eluted from the pulverized polymethacrylic acid using Soxhlet extraction. The binding properties of tetracycline on the MIP were evaluated in methanol by equilibrium rebinding experiements. At the concentration range studied (2-111 µmol/L), the amount of template adsorbed in the polymer increased with increasing initial concentration of template. The binding isotherm of the MIP fitted the Freundlich model with a fairly good correlation (R2= 0.98). A power equation, B= 0.17 [F] 0.29, was obtained giving two binding parameters: pre-exponential factor a = 0.17 and heterogeneity index m=0.29. The Scatchard plot of the binding data of MIP revealed two kinds of binding sites in the MIP. The higher affinity sites had an equilibrium dissociation constant Kd = 2.70 µmol/L and apparent maximum number of sites Bmax = 0.43 µmol/g. For the lower affinity sites, Kd and Bmax, were 20.00 µmol/L and 0.80 µmol/g, respectively. Morphological investigation of the imprinted polymer by SEM, AFM and particle size analyzer was useful in elucidating the nature of molecular imprinting.